2009
DOI: 10.1259/bjr/13217618
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early treatment response after CT-guided radiofrequency ablation of unresectable lung tumours by diffusion-weighted MRI: a pilot study

Abstract: ABSTRACT. The aim of this study was to evaluate prospectively the early treatment response after CT-guided radiofrequency ablation (RFA) of unresectable lung tumours by MRI including diffusion-weighted imaging (DWI). The study protocol was approved by the ethics committee of our hospital and signed consent was obtained from each patient. We studied 17 patients with 20 lung lesions (13 men and 4 women; mean age, 69¡9.8 years; mean tumour size, 20.8¡9.0 mm) who underwent RFA using a LeVeen electrode between Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…If not affected by artifacts, MRI offers good visualization with the same concentric rings aspect as seen on CT. Okuma et al have shown that higher apparent diffusion coefficient values of the tumor measured three days after ablation can predict complete ablation, but there are no other studies confirming these findings [75]. MRI offers no clear advantages over CT except for the lack of radiation, and because of its susceptibility to artifacts and higher costs, MRI follow-up has not become part of the clinical routine in most centers.…”
Section: Mrimentioning
confidence: 99%
“…If not affected by artifacts, MRI offers good visualization with the same concentric rings aspect as seen on CT. Okuma et al have shown that higher apparent diffusion coefficient values of the tumor measured three days after ablation can predict complete ablation, but there are no other studies confirming these findings [75]. MRI offers no clear advantages over CT except for the lack of radiation, and because of its susceptibility to artifacts and higher costs, MRI follow-up has not become part of the clinical routine in most centers.…”
Section: Mrimentioning
confidence: 99%
“…Standard of care imaging therefore fails to differentiate treatment effect from local recurrence in the first year [129]. DW-MRI has potential in this context, as an increasing ADC has been demonstrated following therapy and favours treatment response [131].…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…12) that assess the size, appearance and metabolic activity of the lesion. 14,20,27,34 The WHO criteria are less indexed and also include enhancement and distance dissemination 27 (Fig. 12).…”
Section: B With What Modality?mentioning
confidence: 99%